ANALISIS BENTUK METAFORA DALAM NOVEL TENUN BIRU KARYA UGI AGUSTONO: KAJIAN STILISTIKA - Zulkifli Zulkifli; Desy Ningsih Komalasari (Universitas Batanghari, 2024)
Problem in this research is on a metaphor in a novel Tenun Biru work Ugi Agustono: a stylistic study. Problem of this research are focused on investigating the form, function and meaning of metaphors found in a novel Tenun Biru. There are two benefits of this research namely theoretical and practical benefits and this research use a qualitative method as well as descriptive method. This research using the theory of stylistic pertaining to style of language (figure) to get better results in analyzing form, function and meaning metaphor, as of theory of stylistic considered relevant to inspect figure of a metaphor in a novel. Thus this research get the result of a metaphor comprising a antropormorfic metaphor, sinestic metaphor, abstract into concrete metaphor, dead metaphor, and the life metaphor.